Republic of Lithuania : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This 2014 Article IV Consultation highlights that Lithuania's economy has entered a broadly favorable trajectory of healthy and balanced growth, but income convergence with Western Europe has a long way to go. With inflation at historical lows and well-advanced repair of public finances damaged by the 2008/09 crisis, meeting the entry criteria seems on track. Financial stability has improved further in 2013, with the capital adequacy ratio exceeding 17 percent and steady progress in reducing nonperforming loans. The main challenge is now resuscitating the sluggish private sector credit growth, which could undermine investment and the recovery if it continued for much longer.